Nicht korrekte Aufgaben in dem hilbertschen Raume für lineare Gleichungen mit nicht beschränkten linearen Operatoren - Kuneikaitė, B. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Кунейкайте. Решение некорректной задачи для линейного уравнения с линейным неограниченным симметрическим оператором в гильбертовом пространствеB. Kuneikaitė. Nekorektiško uždavinio su tiesiniu neaprėžtu simetriniu operatoriumi tiesinėms lygtims Hilberto erdvėje sprendimas